Public Service Co-Production and Outcomes: Conceptual Review and Evidence-Based Research Agenda - Sri Lalanawati Octaviani; Harry Nenobais; Johanna Novita (Darul Yasin Al Sys, 2026)
Public service co-production has emerged as a prominent paradigm in contemporary public administration as governments increasingly adopt collaborative approaches to addressing complex societal challenges. However, existing scholarship remains fragmented, frequently emphasizing isolated dimensions such as citizen participation, governance mechanisms, or implementation practices, while comprehensive syntheses integrating conceptual development, theoretical foundations, operational processes, governance challenges, and future research directions remain limited. This study aimed to develop an integrated conceptual understanding of public service co-production and formulate an evidence-based research agenda through a qualitative conceptual review. The study employed document analysis and thematic content analysis, using The Palgrave Handbook of Co-Production of Public Services and Outcomes, comprising 36 chapters authored by leading scholars in the field, as the primary data source. Data were collected through systematic document examination and analyzed through thematic coding and interpretative synthesis. Seven major themes emerged: the conceptual spectrum of co-production, public value outcomes, the Four Co’s operational cycle, implementation and leadership, governance challenges, citizen inclusion and motivation, and future research directions. The findings indicate that co-production has evolved into a multidimensional governance paradigm centered on collaborative public value creation through active interaction among governments, citizens, communities, and other stakeholders. This study contributes to public administration scholarship by consolidating fragmented perspectives into an integrated conceptual framework and proposing a research agenda for advancing theoretical and empirical inquiry. Practically, the findings offer guidance for policymakers and public managers in designing more inclusive, collaborative, and citizen-centered public service systems. Future research should undertake comparative empirical studies across policy sectors and governance contexts while examining the implications of digital transformation and artificial intelligence for public service co-production.